Resource utilization and trophic position of nematodes and harpacticoid copepods in and adjacent to Zostera noltii beds - Vafeiadou, Anna-Maria (2014)
This study examines the resource use and trophic position of nematodes and harpacticoid copepods at the genus/species level in an estuarine food web in Zostera noltii beds and in adjacent bare sediments using the natural abundance of stable carbon and nitrogen isotopes. Microphytobenthos and/or epiphytes are among the main resources of most taxa, but seagrass detritus and sediment particulate organic matter contribute as well to meiobenthos nutrition, which are also available in deeper sediment layers and in unvegetated patches close to seagrass beds. A predominant dependence on chemoautotrophic bacteria was demonstrated for the nematode genus Terschellingia and the copepod family Cletodidae. A predatory feeding mode is illustrated for Paracomesoma and other Comesomatidae, which were previously considered first-level consumers (deposit feeders) according to their buccal morphology. The considerable variation found in both resource use and trophic level among nematode genera from the same feeding type, and even among congeneric nematode species, shows that the interpretation of nematode feeding ecology based purely on mouth morphology should be avoided.